A Trojan Horse in Intensive Care Unit: Toxoplasma gondii. - Can, Özlem Selvi; Yalçin, Saban; Özgencil, Enver; Oba, Sirali; Ünal, Necmettin; Oral, Mehmet; Serdaroglu, Hacer (Turkiye Klinikleri Journal of Medical Sciences, 2012)
ABS TRACT Ob jec ti ve: Toxoplasmosis attains clinical significance as an opportunistic infection with high mortality in immunosuppressed individuals. The aim of this study was to assess the anti-Toxoplasma gondii antibody seropositivity rate in intensive care unit patients (ICU) who are immunosuppressed due to underlying critical illness. Material and Methods: One hundred and three (51 males, 52 females) patients in intensive care units and 78 healthy volunteers (39 males, 39 females) were enrolled in the study. Blood samples were collected from all patients within the first 24 hours of hospitalization in the ICU and anti-T. gondii IgG and IgM antibodies were tested by enzyme-linked immunosorbent assay. Results: IgG antibodies to T. gondii were positive in 58 (56.3%) patients in the ICU and in 19 (24.3%) healthy volunteers. IgM antibodies were positive in 15 patients (13.8%) in the ICU and in five healthy volunteers (6.4%) in the control group. The difference in the IgG seropositivity rate between the patient and the control group was statistically significant (p< 0.05). The seropositivity rate of anti-T.gondii IgM was higher in the patient group with no significance (p> 0.05). Conclusion: Toxoplasma seropositivity is common in ICU patients. Toxoplasmosis should be considered in immunosuppressed patients in the ICU and serological screening may be performed to prevent severe toxoplasmosis.